A novel floating price contract for the ocean freight industry. (1st February 2017) - Yang, Ruina; Gao, Xiaochen; Lee, Chung-Yee
ABSTRACT: In this article, we investigate the carrier–shipper contracting issue arising from the ocean freight industry. In current practice, the carrier may sign a contract with the shipper stating a fixed price per container for the whole year, which is comprised of a low-demand season followed by a high-demand season. By accepting the contract, the shipper agrees to comply with the obligation of transporting the exact number of containers needed in both the low and high seasons at the contracted price. However, often the shipper will default on the committed quantity in the low season when the spot market price drops below the contract price. To address this problem, we propose a floating price contract. In the article, we characterize the optimal contract parameters and the shipper's optimal strategy and evaluate the effectiveness of the floating price contract with a combination of analytical and numerical methods. We find that under a broad class of macroeconomic market conditions, the floating price contract not only enables the carrier to tackle contract default issue more effectively while better enjoying the benefit of capacity planning but makes the shipper better off than relying solely on the spot market.